Shifts in the Recent Distribution of Energy Intake among U.S. Children Aged 2–18 Years Reflect Potential Abatement of Earlier Declining Trends(1)(2)(3) - Mendez, Michelle A. (American Society for Nutrition, 2014)
Recent national surveys suggest that child obesity in the United States may have reached a plateau, but corresponding trends in energy intake have not been examined in depth. This article evaluates medium-term trends in children’s reported energy intake by using 4 waves of national dietary surveillance from 2003–2004 to 2009–2010. The analysis uses up to 2 24-h dietary recalls, incorporating methods that address challenges in estimating usual intake, accounting for intraindividual variance and covariates such as the presence of atypical consumption days. Quantile regression was used to assess disparities in intake among sociodemographic subgroups at extremes of the distribution as well as at the median, and the potential influence of misreporting was evaluated. Results indicated that after an initial decline in intakes across all age groups through 2007–2008, there were significant increases of ∼90 kcal/d at the median among adolescents in 2009–2010, whereas intakes in younger children remained steady. Among adolescent boys, the recent increase was larger at the 90th percentile than at the median. Intake trends did not vary by race/ethnic group, among whom intakes were similar at the upper end of the distribution. Misreporting did not influence trends over time, but intakes were lower in younger children and higher in older children after excluding misreporters. Overall, findings suggest that declines in children’s energy intake from 2003–2004 through 2007–2008 were consistent with the obesity plateau observed in most age and gender subgroups through 2009–2010. However, there is evidence of increased intakes among adolescents in 2009–2010, which may threaten the earlier abatement in overweight in this older age group.